Using the Mirror as a Working Tool in Handicraft Education (The 40th International Pupils’ Attitudes Towards Technology Conference Proceedings 2023, 2023)
In interaction between students and vocational teachers, technical artefacts constitute an essential part for the development of vocational students’ future professional knowledge. Although vocational learning has been an under-researched area, there has been an increased interest within the vocational education research to examine the teaching and learning processes that take place when vocational students and teachers interact in vocational school settings. The presence of physical objects such as tools, machines and material in the teaching and learning processes within vocational education, which encompass a central aspect of a vocational subjects’ specific characteristics, is a dimension which is often overlooked. In the Handicraft programme (specialization hair- and makeup stylist) at Swedish upper secondary vocational education, a large part of the practical work that students are engaged in is to view their work through the mirror. Therefore, the focus in this study is what learning content is made relevant when teacher and student(s) are interacting in front of the mirror. The data for the study consists of video recorded lessons from the Handicraft Programme, and the study is based on CAVTA (Conversation Analysis and Variation Theory). Based on CAVTA, the process of learning includes what is being learned and how learning is done in interaction between the teacher and student(s) in the authentic and enacted teaching session. At the conference, we will present results from detailed analysis of sequences when the teacher and the students interact in front of the mirror and what vocational knowledge is made possible to learn in these interactions.